Solid electrolyte coated lithium-doped graphite composite material as well as preparation method and application thereof
The solid electrolyte-coated lithium-doped graphite composite material addresses ion conductivity deviations in lithium-ion batteries by enhancing ionic and electronic conductivity, improving fast charging and low-temperature performance through a core-shell structure with synergistic effects.
Patent Information
- Application Number
- CN202411386342.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-13
AI Technical Summary
Existing lithium-ion battery negative electrode materials, such as soft carbon or hard carbon, exhibit ion conductivity deviations under low temperature conditions, leading to power performance deviations and slow lithium ion and electron diffusion rates, which affect fast charging and low-temperature performance.
A solid electrolyte-coated lithium-doped graphite composite material is developed, comprising a core of lithium, a first conductive agent, and graphite, with a shell of a solid electrolyte, a second conductive agent, and amorphous carbon, where the solid electrolyte and second conductive agent are co-doped in the amorphous carbon, enhancing ionic and electronic conductivity through synergistic effects.
The composite material improves fast charging and low-temperature performance by increasing lithium ion transmission rates and reducing defects, resulting in better discharge capacity, efficiency, and cycle performance.
Smart Images

Figure CN119133413A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a solid electrolyte-coated lithium-doped graphite composite material, and a preparation method and application thereof. Background Art
[0002] With the increasing market demand for low-temperature lithium-ion batteries, lithium-ion batteries are required to have excellent low-temperature charging and discharging capabilities under low-temperature conditions, and the negative electrode material is a key material that affects the low-temperature performance of the battery.
[0003] At present, the negative electrode materials on the market are mainly artificial graphite, and soft carbon or hard carbon is coated in its shell. Relying on its high lithium ion diffusion coefficient under low temperature conditions, the insertion and extraction rate of lithium ions in the material is improved. However, soft carbon or hard carbon currently has defects such as ion conductivity deviation under low temperature conditions, which causes its power performance deviation under low temperature conditions. Therefore, it is necessary to dope or coat it to improve the electronic or ionic conductivity of the material. Solid electrolytes have the characteristics of high ionic conductivity and stable structure. On the one hand, coating on the surface of the material reduces the surface defects of the material and improves the initial efficiency. On the other hand, it increases the transmission rate of lithium ions during charging and discharging to improve the cycle performance. At the same time, compared with amorphous carbon, solid electrolytes have the advantages of stable structure and good ionic conductivity, but the electronic conductivity of the material is poor, so it needs to be mixed with materials with electronic conductivity to improve the low temperature performance of the material. For example, patent application No. CN202210926442.3 discloses an artificial solid electrolyte-coated lithium-doped graphite composite material and its preparation method, which presents a core-shell structure, with the core being artificial graphite, and the outer shell being composed of 0.5% to 2% lithium borate, 1% to 5% solid electrolyte, 0.5% to 2% conductive agent and amorphous carbon. Although the rate and initial efficiency of the material are improved, the diffusion rate of ions and electrons in the artificial graphite in the core of the material is slow, resulting in deviations in the material's fast charging performance and low-temperature performance. Summary of the invention
[0004] Based on this, it is necessary to provide a lithium-doped graphite composite material with better fast charging performance and low temperature performance.
[0005] In addition, it is also necessary to provide a solid electrolyte coated lithium-doped graphite composite material and a preparation method thereof, as well as an application of the solid electrolyte coated lithium-doped graphite composite material.
[0006] A solid electrolyte-coated lithium-doped graphite composite material comprises an inner core and an outer shell coated outside the inner core, wherein the materials of the inner core are lithium, a first conductive agent and graphite, the lithium and the first conductive agent are coated together on the graphite surface, the materials of the outer shell comprise a solid electrolyte, a second conductive agent and amorphous carbon, the solid electrolyte and the second conductive agent are doped together in the amorphous carbon; the mass ratio of the inner core to the outer shell is 85-95:5-15.
[0007] In one embodiment, in the core, the mass ratio of the lithium, the first conductive agent and the graphite is 2-10:3-10:80-95.
[0008] In one embodiment, in the shell, the mass ratio of the solid electrolyte, the second conductive agent and the amorphous carbon is 10-30:5-10:60-85.
[0009] In one embodiment, the first conductive agent is a carbon nanotube, and the second conductive agent is at least one of a carbon nanotube, graphene, and carbon black;
[0010] The solid electrolyte is selected from LiZr2(PO4)3, Li7La3Zr2O 12 , Li2ZrCl6, Li3N, La 0.61 Li 0.17 TiO3 and Li 10 Ge 0.5 Sn 0.5 At least one of P2S11Se.
[0011] A method for preparing the above-mentioned solid electrolyte coated lithium-doped graphite composite material comprises the following steps:
[0012] According to the mass ratio of lithium: first organic solvent: first conductive agent: graphite: asphalt = 5-10:500:1-5:100:5-10, under a protective gas atmosphere, the lithium is added to the organic solvent, then the first conductive agent is added, dispersed evenly and fully soaked, and finally the graphite and asphalt are added, mixed evenly and filtered, and the obtained filter residue is carbonized to obtain an intermediate;
[0013] According to the mass ratio of solid electrolyte: second conductive agent: dispersant: intermediate = 1-5: 0.5-2: 0.5-2: 100, the solid electrolyte is added to the second organic solvent to prepare a solution with a concentration of 1wt%-10wt%, then the second conductive agent and the dispersant are added to obtain a coating liquid, and finally the intermediate is added, and the mixture is evenly dispersed and dried, and the dried product is carbonized again to obtain the required lithium-doped graphite composite material, wherein the lithium-doped graphite composite material includes a core and a shell coated outside the core, the material of the core is lithium, a first conductive agent and graphite, the lithium and the first conductive agent are jointly coated on the graphite surface, the material of the shell includes a solid electrolyte, a second conductive agent and amorphous carbon, and the solid electrolyte and the second conductive agent are jointly doped in the amorphous carbon; the mass ratio of the core to the shell is 85-95: 5-15.
[0014] In one embodiment, the first organic solvent is biphenyl;
[0015] In the operation of carbonizing the obtained filter residue, the carbonization temperature is 900° C. to 1200° C., and the carbonization time is 1 h to 6 h.
[0016] In one embodiment, the second organic solvent is N-methylpyrrolidone;
[0017] The dispersant is selected from at least one of polyvinyl pyrrolidone, polyacrylamide and polyethylene glycol;
[0018] In the operation of drying after uniform dispersion and re-carbonizing the dried product, the drying is spray drying, the re-carbonization temperature is 1100° C. to 1300° C., and the re-carbonization time is 1 hour to 6 hours.
[0019] In one embodiment, the operation of adding the solid electrolyte to the second organic solvent to prepare a solution with a concentration of 1 wt % to 10 wt % is: adding the solid electrolyte to the second organic solvent to prepare a solution with a concentration of 1 wt % to 5 wt %.
[0020] In one embodiment, the first conductive agent is a carbon nanotube, and the second conductive agent is at least one of a carbon nanotube, graphene, and carbon black;
[0021] The solid electrolyte is selected from LiZr2(PO4)3, Li7La3Zr2O 12 , Li2ZrCl6, Li3N, La 0.61 Li 0.17 TiO3 and Li 10 Ge 0.5 Sn 0.5 At least one of P2S11Se.
[0022] Application of the above-mentioned solid electrolyte coated lithium-doped graphite composite material in the field of secondary battery negative electrode materials.
[0023] The solid electrolyte-coated lithium-doped graphite composite material of the present invention comprises an inner core and an outer shell coated outside the inner core, the material of the outer shell comprises a solid electrolyte, a second conductive agent and amorphous carbon, and the solid electrolyte and the second conductive agent are co-doped in the amorphous carbon, the presence of the amorphous carbon in the outer shell improves the coating effect and its strength, relies on the high ionic conductivity of the solid electrolyte in the outer shell and the electronic conductivity of the second conductive agent, and exerts the synergistic effect between the two, thereby improving the electronic and ionic conductivity of the lithium-doped graphite composite material during the charge and discharge process, and improving the fast charging and low-temperature performance of the lithium-doped graphite composite material.
[0024] Compared with traditional materials, the lithium-doped graphite composite material of the present invention has better fast charging performance and low-temperature performance.
[0025] In addition, the core material of the solid electrolyte lithium-doped graphite composite material of the present invention is lithium, a first conductive agent and graphite, and lithium and the first conductive agent are coated on the graphite surface together, thereby improving the ionic and electronic conductivity of the lithium-doped graphite composite material.
[0026] In addition, the first conductive agent in the shell of the solid electrolyte coated lithium-doped graphite composite material of the present invention has excellent liquid retention performance and high electronic conductivity, the inner core reduces defects by lithium-doped graphite to increase the number of lithium ions during the charging and discharging process, and produces a synergistic effect with the solid electrolyte with high ion transfer rate in the shell, thereby improving the low-temperature performance, rate performance and initial efficiency of the solid electrolyte coated lithium-doped graphite composite material.
[0027] In the preparation method of the solid electrolyte coated lithium-doped graphite composite material of the present invention, asphalt is added as a binder to improve the coating effect and strength of the shell, and the amorphous carbon obtained after carbonization of the asphalt is also convenient for doping with the solid electrolyte and the second conductive agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] in:
[0030] Figure 1The present invention is a flow chart of a method for preparing a solid electrolyte-coated lithium-doped graphite composite material according to one embodiment.
[0031] Figure 2 This is a SEM image of the solid electrolyte-coated lithium-doped graphite composite material prepared in Example 1. DETAILED DESCRIPTION
[0032] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described below with reference to the accompanying drawings.
[0033] The present invention discloses a lithium-doped graphite composite material of an embodiment, comprising a core and a shell coated outside the core, wherein the core is made of lithium, a first conductive agent and graphite, the lithium and the first conductive agent are coated on the surface of the graphite, the shell comprises a solid electrolyte, a second conductive agent and amorphous carbon, and the solid electrolyte and the second conductive agent are doped in the amorphous carbon. The mass ratio of the core to the shell is 85-95:5-15.
[0034] The solid electrolyte coated lithium doped graphite composite material of the present invention comprises an inner core and an outer shell coated outside the inner core, the material of the outer shell comprises a solid electrolyte, a second conductive agent and amorphous carbon, and the solid electrolyte and the second conductive agent are co-doped in the amorphous carbon, the presence of the amorphous carbon in the outer shell improves the coating effect and its strength, relies on the high ionic conductivity of the solid electrolyte in the outer shell and the electronic conductivity of the second conductive agent, and exerts the synergistic effect between the two, thereby improving the electronic and ionic conductivity of the solid electrolyte coated lithium doped graphite composite material during charging and discharging, and improving the fast charging and low temperature performance of the solid electrolyte coated lithium doped graphite composite material.
[0035] Compared with traditional materials, the solid electrolyte-coated lithium-doped graphite composite material of the present invention has better fast charging performance and low-temperature performance.
[0036] In addition, the core material of the solid electrolyte-coated lithium-doped graphite composite material of the present invention is lithium, a first conductive agent and graphite, and lithium and the first conductive agent are co-coated on the graphite surface, thereby improving the ionic and electronic conductivity of the lithium-doped graphite composite material.
[0037] In addition, the first conductive agent in the shell of the lithium-doped graphite composite material of the present invention has excellent liquid retention performance and high electronic conductivity. The inner core reduces defects by lithium-doped graphite to increase the number of lithium ions during the charging and discharging process, and produces a synergistic effect with the solid electrolyte with high ion transfer rate in the shell, thereby improving the low-temperature performance, rate performance and initial efficiency of the solid electrolyte-coated lithium-doped graphite composite material.
[0038] Preferably, in the core of the lithium-doped graphite composite material of this embodiment, the mass ratio of lithium, the first conductive agent and graphite is 2-10:3-10:80-95.
[0039] Preferably, in the outer shell of the lithium-doped graphite composite material of this embodiment, the mass ratio of the solid electrolyte, the second conductive agent and the amorphous carbon is 10-30:5-10:60-85.
[0040] Specifically, in this embodiment, the first conductive agent may be a carbon nanotube, and the second conductive agent may be at least one of a carbon nanotube, graphene, and carbon black.
[0041] Specifically, in this embodiment, the solid electrolyte can be selected from LiZr2(PO4)3, Li7La3Zr2O 12 , Li2ZrCl6, Li3N, La 0.61 Li 0.17 TiO3 and Li 10 Ge 0.5 Sn 0.5 At least one of P2S11Se.
[0042] Combination Figure 1 The present invention discloses a method for preparing the above-mentioned lithium-doped graphite composite material in one embodiment, comprising the following steps:
[0043] S10. According to the mass ratio of lithium: first organic solvent: first conductive agent: graphite: asphalt = 5-10:500:1-5:100:5-10, under a protective gas atmosphere, lithium is added to the organic solvent, and then the first conductive agent is added, and after being evenly dispersed, it is fully soaked, and finally graphite and asphalt are added, and after being evenly mixed, it is filtered, and the obtained filter residue is carbonized to obtain an intermediate.
[0044] The protective gas atmosphere may be a nitrogen atmosphere, a helium atmosphere, a neon atmosphere, an argon atmosphere, a krypton atmosphere, or a xenon atmosphere.
[0045] Preferably, in this embodiment, the first organic solvent is biphenyl.
[0046] Preferably, in this embodiment, the first conductive agent is carbon nanotubes.
[0047] Preferably, in this embodiment, the solid electrolyte is selected from LiZr2(PO4)3, Li7La3Zr2O 12 , Li2ZrCl6, Li3N, La 0.61 Li 0.17 TiO3 and Li 10 Ge 0.5 Sn 0.5 At least one of P2S11Se.
[0048] Preferably, in the operation of carbonizing the obtained filter residue in S10, the carbonization temperature is 900° C. to 1200° C., and the carbonization time is 1 h to 6 h.
[0049] In this embodiment, asphalt is used as a binder to mix and adhere the conductive agent, graphite and lithium together and then carbonize them.
[0050] By adding asphalt as a binder, the coating effect and strength of the solid electrolyte coated lithium-doped graphite composite material finally prepared are improved, and the amorphous carbon obtained after carbonization of the asphalt is also convenient for the subsequent doping of the solid electrolyte and the second conductive agent.
[0051] Specifically, in this embodiment, the graphite may be artificial graphite. The graphite is added in the form of powder with a particle size of 5 to 20 μm.
[0052] S20. According to the mass ratio of solid electrolyte: second conductive agent: dispersant: intermediate = 1 to 5: 0.5 to 2: 0.5 to 2: 100, the solid electrolyte is added to the second organic solvent to prepare a solution with a concentration of 1 wt% to 10 wt%, and then the second conductive agent and the dispersant are added to obtain a coating liquid, and finally the intermediate is added, and the mixture is dried after being evenly dispersed, and the dried product is carbonized again to obtain the desired lithium-doped graphite composite material.
[0053] The solid electrolyte coated lithium doped graphite composite material includes a core and a shell coated outside the core, the core material is lithium, a first conductive agent and graphite, the lithium and the first conductive agent are co-coated on the graphite surface, the shell material includes a solid electrolyte, a second conductive agent and amorphous carbon, the solid electrolyte and the second conductive agent are co-doped in the amorphous carbon. The mass ratio of the core to the shell is 85-95:5-15.
[0054] It should be noted that, in this embodiment, the second conductive agent is added in the form of a solution, so that the second conductive agent can be evenly dispersed.
[0055] Preferably, in this embodiment, the second organic solvent is N-methylpyrrolidone.
[0056] Preferably, in this embodiment, the second conductive agent is at least one of carbon nanotubes, graphene and carbon black.
[0057] Preferably, in this embodiment, the dispersant is selected from at least one of polyvinyl pyrrolidone, polyacrylamide and polyethylene glycol.
[0058] Preferably, in S20, after being uniformly dispersed, the product is dried and then carbonized again, wherein the drying is spray drying, the temperature of the carbonization again is 1100° C. to 1300° C., and the time of the carbonization again is 1 h to 6 h.
[0059] Preferably, in S20, the solid electrolyte is added to the second organic solvent to prepare a solution with a concentration of 1 wt% to 5 wt%.
[0060] The solid electrolyte coated lithium-doped graphite composite material can be applied to the field of secondary battery negative electrode materials.
[0061] Specifically, the lithium-doped graphite composite material can be used as a negative electrode material for lithium-ion batteries.
[0062] The following are specific embodiments.
[0063] In a specific embodiment, artificial graphite is EMG-P purchased from Shanghai Shanshan Technology Co., Ltd., asphalt is 180# purchased from Liaoning Xinde New Materials Technology Co., Ltd., carbon nanotubes are LB107-44 purchased from Jiangsu Tiannai Technology Co., Ltd., graphene is DZL-012 purchased from Shandong Dazhan Nanomaterials Co., Ltd., carbon black is EH700 purchased from Jiaozuo Hexing Chemical Co., Ltd., LiZr2(PO4)3 is CAS, 12031-83-3 purchased from Anhui Keda Pu Rui Co., Ltd., Li7La3Zr2O 12 The TOB-LIZO model was purchased from Shenzhen Liyou New Energy Technology Co., Ltd., and Li2ZrCl6 was purchased from Shenzhen Liyou New Energy Technology Co., Ltd. as TOB-LIZCL model.
[0064] Example 1
[0065] A method for preparing a solid electrolyte-coated lithium-doped graphite composite material comprises the following steps:
[0066] Step S1:
[0067] Under an argon inert atmosphere, 8 g of metallic lithium was added to 500 g of biphenyl organic solvent, and then 3 g of carbon nanotubes were added and dispersed evenly and soaked for 24 h. Then 100 g of artificial graphite and 3 g of asphalt were added and mixed evenly. The mixture was filtered and the residue was carbonized at 1100 °C for 3 h to obtain an intermediate.
[0068] Step S2:
[0069] 3g LiZr2(PO4)3 was added to 60g N-methylpyrrolidone organic solvent to prepare a 5wt% solution, and then 33g of 3wt% carbon nanotube conductive agent solution and 1g polyvinylpyrrolidone were added to prepare a coating solution, and then 100g of the intermediate material was added and dispersed evenly, spray dried (inlet temperature 200℃, outlet temperature 80℃, flow rate 1kg / h, 1h), and the obtained material was carbonized at 1200℃ for 3h to obtain a solid electrolyte coated lithium-doped graphite composite material.
[0070] Example 2
[0071] A method for preparing a solid electrolyte-coated lithium-doped graphite composite material comprises the following steps:
[0072] Step S1:
[0073] Under an argon inert atmosphere, 5 g of metallic lithium was added to 500 g of biphenyl organic solvent, and then 1 g of carbon nanotubes was added and dispersed evenly and soaked for 24 h, and then 100 g of artificial graphite and 5 g of asphalt were added and mixed evenly, filtered, and the obtained filter residue was carbonized at 900 ° C for 6 h to obtain an intermediate;
[0074] Step S2:
[0075] 1g Li7La3Zr2O 12 The mixture was added into 100g N-methylpyrrolidone organic solvent to prepare a 1wt% solution, and then 50g of 1wt% graphene conductive agent solution and 0.5g polyacrylamide were added to prepare a coating solution, and then 100g of the intermediate material was added to disperse evenly, and spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 1kg / h, 1h). The obtained material was carbonized at 1100°C for 6h to obtain a solid electrolyte-coated lithium-doped graphite composite material.
[0076] Example 3
[0077] A method for preparing a solid electrolyte-coated lithium-doped graphite composite material comprises the following steps:
[0078] Step S1:
[0079] Under an argon inert atmosphere, 10 g of metallic lithium was added to 500 g of biphenyl organic solvent, and then 5 g of carbon nanotubes were added and dispersed evenly and soaked for 24 h, and then 100 g of artificial graphite and 10 g of asphalt were added and mixed evenly, filtered, and the obtained filter residue was carbonized at 1200 ° C for 1 h to obtain an intermediate;
[0080] Step S2:
[0081] 5g Li2ZrCl6 was added to 50g N-methylpyrrolidone organic solvent to prepare a 10wt% solution, and then 40g of 5wt% carbon black conductive agent solution and 2g polyethylene glycol were added to prepare a coating solution, and then 100g of the intermediate material was added and dispersed evenly, spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 1kg / h, 1h), and the obtained material was carbonized at 1300°C for 1h to obtain a solid electrolyte-coated lithium-doped graphite composite material.
[0082] Comparative Example 1
[0083] Comparative Example 1 is substantially the same as Example 1, except that no LiZr2(PO4)3 solid electrolyte is added in step S2.
[0084] Specifically, the steps are as follows:
[0085] A method for preparing a solid electrolyte-coated lithium-doped graphite composite material comprises the following steps:
[0086] Step S1:
[0087] Under an argon inert atmosphere, 8 g of metallic lithium was added to 500 g of biphenyl organic solvent, and then 3 g of carbon nanotubes were added and dispersed evenly and soaked for 24 h. Then 100 g of artificial graphite and 3 g of asphalt were added and mixed evenly. The mixture was filtered and the residue was carbonized at 1100 °C for 3 h to obtain an intermediate.
[0088] Step S2:
[0089] To 60g of N-methylpyrrolidone organic solvent, 33g of 3wt% carbon nanotube conductive agent solution and 1g of polyvinylpyrrolidone were added to prepare a coating liquid, and then 100g of the intermediate material was added and dispersed evenly, and spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 1kg / h, 1h). The obtained material was carbonized at 1200°C for 3h to obtain a graphite composite material.
[0090] Comparative Example 2
[0091] Comparative Example 2 is substantially the same as Example 1, except that metallic lithium is not added in step S1.
[0092] Specifically, the steps are as follows:
[0093] A method for preparing a solid electrolyte-coated lithium-doped graphite composite material comprises the following steps:
[0094] Step S1:
[0095] Under an argon inert atmosphere, 3 g of carbon nanotubes were added to 500 g of biphenyl organic solvent, dispersed evenly and soaked for 24 h, then 100 g of artificial graphite and 3 g of asphalt were added and mixed evenly, filtered, and the resulting filter residue was carbonized at 1100 ° C for 3 h to obtain an intermediate.
[0096] Step S2:
[0097] 3g LiZr2(PO4)3 was added to 60g N-methylpyrrolidone organic solvent to prepare a 5wt% solution, and then 33g of 3wt% carbon nanotube conductive agent solution and 1g polyvinylpyrrolidone were added to prepare a coating solution, and then 100g of the intermediate material was added and dispersed evenly, spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 1kg / h, 1h), and the obtained material was carbonized at 1200°C for 3h to obtain a graphite composite material.
[0098] Test Case
[0099] (1) SEM test
[0100] The solid electrolyte coated lithium-doped graphite composite material prepared in Example 1 was subjected to SEM testing, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that the solid electrolyte-coated lithium-doped graphite composite material prepared in Example 1 is spherical in shape, with a particle size between 5 μm and 10 μm and a uniform size distribution.
[0101] (2) Physical and chemical properties test
[0102] According to the test method in the standard GB / T-24533-2019 "Graphite Negative Electrode Materials for Lithium Ion Batteries", the powder resistivity, tap density, and specific surface area of the solid electrolyte-coated lithium-doped graphite composite materials prepared in Examples 1-3 and the graphite composite materials prepared in Comparative Examples 1-2 were tested, respectively. The OI value of the powder material was tested by XRD, the diffusion coefficient was tested by GITT, and the material interlayer spacing D002 was tested by XRD. The test results are shown in Table 1.
[0103] Table 1
[0104]
[0105] It can be seen from Table 1 that the diffusion coefficient, powder resistivity and OI value of the solid electrolyte-coated lithium-doped graphite composite materials prepared in Examples 1-3 are significantly better than those of Comparative Examples 1-2. The reason may be that the solid electrolyte with a high lithium ion transmission rate on the surface of the solid electrolyte-coated lithium-doped graphite composite materials prepared in Examples 1-3 improves the lithium ion diffusion rate of the material and its doped metallic lithium forms lithium ions during the charge and discharge process, which improves the diffusion rate of the material and changes the orientation of carbon, thereby reducing the OI value.
[0106] (3) Button battery test
[0107] The solid electrolyte-coated lithium-doped graphite composite materials prepared in Examples 1-3 and the graphite composite materials prepared in Comparative Examples 1-2 were respectively assembled into button batteries according to the following methods:
[0108] The solid electrolyte-coated lithium-doped graphite composite material prepared in Examples 1-3 and the graphite composite material prepared in Comparative Examples 1-2 were used as negative electrodes, and assembled into button cells with lithium sheets, electrolytes and diaphragms in a glove box with argon and water content less than 0.1ppm. The diaphragm was celegard 2400; the electrolyte was a solution of LiPF6, in which the concentration of LiPF6 was 1 mol / L, and the solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) mixed in a weight ratio of 1:1.
[0109] The button cells were tested for their performance using a blue battery tester. The test conditions were: 0.1C rate charge and discharge, voltage range 0.005-2V, 3 cycles, then stopped, and then tested for discharge capacity under 1C conditions; at the same time, tested for 0.1 specific capacity at low temperature -20°C, calculated for low temperature capacity retention, cycle performance (25±3°C, 0.2C / 0.2C, 100 cycles) and room temperature charging DCR (50% SOC). The test results are shown in Table 2.
[0110] Table 2
[0111]
[0112] As can be seen from Table 2, the button cell made of the solid electrolyte coated lithium-doped graphite composite material prepared in Examples 1-3 has a significantly higher discharge capacity and efficiency than that of Comparative Examples 1-2. The experimental results show that the solid electrolyte coated lithium-doped graphite composite material prepared in Examples 1-3 can make the battery have good discharge specific capacity and efficiency; the reason is that the surface-coated solid electrolyte in the graphite has excellent lithium ion conductivity, which improves the initial efficiency and its low-temperature performance; at the same time, the core is doped with metallic lithium, which releases lithium ions during the charge and discharge process, reduces its irreversible capacity, and improves the initial efficiency and its cycle performance.
[0113] (4) Soft-pack battery performance test
[0114] The solid electrolyte coated lithium-doped graphite composite material prepared in Examples 1-3 and the graphite composite material prepared in Comparative Examples 1-2 were used as negative electrode active materials, and the positive electrode active material ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2), electrolyte and diaphragm are assembled into 5Ah soft pack batteries. The diaphragm is celegard 2400, and the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.3mol / L). The prepared soft pack batteries are marked as A-2, B-2, C-2, D-2, and E-2, and the cycle performance and rate performance of the battery are tested. The test results are detailed in Table 3.
[0115] Among them, the cycle performance: the battery cycle performance is tested at a charge and discharge rate of 2C / 2C, a voltage range of 2.8V-4.2V, a cycle number of 500 cycles, and a temperature of 25±3℃;
[0116] Among them, rate performance: at a rate of 2C, the battery is charged to 100% SOC using constant current + constant voltage mode, and then the constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity) is calculated.
[0117] Table 3
[0118]
[0119] It can be seen from Table 3 that the cycle performance and fast charging performance of the soft-pack battery of the solid electrolyte-coated lithium-doped graphite composite material prepared by Examples 1-3 are significantly better than those of Comparative Examples 1-2. The reason is that the solid electrolyte-coated lithium-doped graphite composite material prepared by Examples 1-3 has a solid electrolyte coated on the surface to reduce the consumption of lithium ions during the charge and discharge process and its large specific surface area, thereby improving its cycle performance; at the same time, the solid electrolyte-coated lithium-doped graphite composite material prepared by Examples 1-3 has an excellent diffusion coefficient and a low OI value, thereby improving the fast charging performance of the material.
[0120] In the description of the embodiments of the present invention, it should be noted that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limitations on the embodiments of the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0121] In the description of the embodiments of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.
[0122] In the embodiments of the present invention, unless otherwise clearly specified and limited, the first feature being "above" or "below" the second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, the first feature being "above", "above" and "above" the second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. The first feature being "below", "below" and "below" the second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0123] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid electrolyte coated lithium-doped graphite composite material, characterized in that: The invention comprises an inner core and an outer shell coated on the outer core, wherein the materials of the inner core are lithium, a first conductive agent and graphite, the lithium and the first conductive agent are coated on the graphite surface together, the materials of the outer shell comprise a solid electrolyte, a second conductive agent and amorphous carbon, the solid electrolyte and the second conductive agent are doped in the amorphous carbon together; the mass ratio of the inner core to the outer shell is 85-95:5-15.
2. The lithium-doped graphite composite material according to claim 1, characterized in that: In the core, the mass ratio of the lithium, the first conductive agent and the graphite is 2-10:3-10:80-95.
3. The lithium-doped graphite composite material according to claim 1, characterized in that: In the shell, the mass ratio of the solid electrolyte, the second conductive agent and the amorphous carbon is 10-30:5-10:60-85.
4. The lithium-doped graphite composite material according to any one of claims 1 to 3, characterized in that: The first conductive agent is a carbon nanotube, and the second conductive agent is at least one of a carbon nanotube, graphene and carbon black; The solid electrolyte is selected from LiZr2(PO4)3, Li7La3Zr2O 12 , Li2ZrCl6, Li3N, La 0.61 Li 0.17 TiO3 and Li 10 Ge 0.5 Sn 0.5 At least one of P2S11Se.
5. A method for preparing a lithium-doped graphite composite material according to any one of claims 1 to 4, characterized in that: The steps include: According to the mass ratio of lithium: first organic solvent: first conductive agent: graphite: asphalt = 5-10:500:1-5:100:5-10, under a protective gas atmosphere, the lithium is added to the organic solvent, then the first conductive agent is added, dispersed evenly and fully soaked, and finally the graphite and asphalt are added, mixed evenly and filtered, and the obtained filter residue is carbonized to obtain an intermediate; According to the mass ratio of solid electrolyte: second conductive agent: dispersant: intermediate = 1-5: 0.5-2: 0.5-2: 100, the solid electrolyte is added to the second organic solvent to prepare a solution with a concentration of 1wt%-10wt%, then the second conductive agent and the dispersant are added to obtain a coating liquid, and finally the intermediate is added, and the mixture is evenly dispersed and dried, and the dried product is carbonized again to obtain the required lithium-doped graphite composite material, wherein the lithium-doped graphite composite material includes a core and a shell coated outside the core, the material of the core is lithium, a first conductive agent and graphite, the lithium and the first conductive agent are jointly coated on the graphite surface, the material of the shell includes a solid electrolyte, a second conductive agent and amorphous carbon, and the solid electrolyte and the second conductive agent are jointly doped in the amorphous carbon; the mass ratio of the core to the shell is 85-95: 5-15.
6. The method for preparing the lithium-doped graphite composite material according to claim 5, characterized in that: The first organic solvent is biphenyl; In the operation of carbonizing the obtained filter residue, the carbonization temperature is 900° C. to 1200° C., and the carbonization time is 1 h to 6 h.
7. The method for preparing the lithium-doped graphite composite material according to claim 5, characterized in that: The second organic solvent is N-methylpyrrolidone; The dispersant is selected from at least one of polyvinyl pyrrolidone, polyacrylamide and polyethylene glycol; In the operation of drying after uniform dispersion and re-carbonizing the dried product, the drying is spray drying, the re-carbonization temperature is 1100° C. to 1300° C., and the re-carbonization time is 1 hour to 6 hours.
8. The method for preparing the lithium-doped graphite composite material according to claim 7, characterized in that: The operation of adding the solid electrolyte into the second organic solvent to prepare a solution with a concentration of 1 wt% to 10 wt% is: adding the solid electrolyte into the second organic solvent to prepare a solution with a concentration of 1 wt% to 5 wt%.
9. The method for preparing the lithium-doped graphite composite material according to any one of claims 5 to 8, characterized in that: The first conductive agent is a carbon nanotube, and the second conductive agent is at least one of a carbon nanotube, graphene and carbon black; The solid electrolyte is selected from LiZr2(PO4)3, Li7La3Zr2O 12 , Li2ZrCl6, Li3N, La 0.61 Li 0.17 TiO3 and Li 10 Ge 0.5 Sn 0.5 At least one of P2S11Se.
10. Use of the lithium-doped graphite composite material according to any one of claims 1 to 4 in the field of secondary battery negative electrode materials.
Citation Information
Patent Citations
Artificial graphite composite material and preparation method thereof
CN115241526A
